Parental Experiences of Raising a Child With Medium Chain Acyl-CoA Dehydrogenase Deficiency - Hilary Piercy; Katarzyna Machaczek; Parveen Ali; Sufin Yap (SAGE Publishing, 2017)
Newborn screening enabling early diagnosis of medium chain acyl-CoA dehydrogenase deficiency (MCADD) has dramatically improved health outcomes in children with MCADD. Achieving those outcomes depends on effective management by parents. Understanding parental management strategies and associated anxieties and concerns is needed to inform provision of appropriate care and support. Semistructured interviews were conducted with a purposive sample of parents of children aged 2 to 12 years. Thematic analysis identified two main themes. Managing dietary intake examined how parents managed day-to-day dietary intake to ensure adequate intake and protection of safe fasting intervals. Managing and preventing illness events explored parental experiences of managing illness events and their approach to preventing these events. Management strategies were characterized by caution and vigilance and influenced by a lack of confidence in others to manage the condition. The study identifies the need for increased awareness of the condition, particularly in relation to emergency treatment.